Peningkatan Kompetensi Digitalisasi Pelaku UMKM pada Forum UMKM Cikarang Pusat - Yuningsih, Nining; Mardiputra, Ilham Muhammad; Hidayati, Rika Nur; Ramdani, M R Rafli (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
Increasing the competence of MSME players in the Bekasi Regency area needs to be improved in the digital era. One of the challenges for the Cikarang Centre MSME Forum is the lack of understanding of the importance of digital-based business management. The purpose of this training is to enhance the knowledge and practical skills of MSME players, enabling them to adopt digital technology in managing HR, particularly in the context of e-commerce. This activity involved 15 participants at Balai Deas Cikarang Pusat. The results of the activity showed a significant increase in the understanding of e-commerce, especially Product Search Engine Optimisation and Product Photos. thus successfully changing the level of confidence and ability of MSME implementation from the phase of knowing to mastering the basics of digital operations. The implication of the activity is expected to be sustainable, facilitating the adoption of technologies such as Artificial Intelligence (AI) in creating product photos and preparing MSMEs to enter a more advanced stage of innovation.ABSTRAKPeningkatan kompetensi pelaku UMKM di wilayah Kabupaten Bekasi perlu ditingkatkan dalam menghadapi era digital. Salah satu yang menjadi tantangan pada Forum UMKM Cikarang Pusat adalah kurangnya pemahaman yang penting dalam me manage usaha berbasis digital. Tujuan dari pelatihan ini adalah meningkatkan pengetahuan dan keterampilan praktis pelaku UMKM agar mampu mengadopsi teknologi digital dalam mengelola SDM terutama mengenai e-commerce. Kegiatan ini melibatkan 15 peserta di Balai Desa Cikarang Pusat. Hasil kegiatan menunjukkan peningkatan yang signifikan pada pemahaman e-commerce, terutama Search Engine Optimization Produk dan Foto Produk. sehingga berhasil mengubah tingkat kepercayaan dan kemampuan implementasi UMKM dari fase mengenal menjadi menguasai dasar-dasar operasional digital. Implikasi kegiatan diharapkan dapat berkelanjutan atas adopsi teknologi seperti Artificial Intelligence (AI) dalam pembuatan foto produk yang juga diperkenalkan, dan mempersiapkan UMKM untuk memasuki tahap inovasi yang lebih maju.